2020
DOI: 10.3390/su12166413
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Business Model to Measure Organizational and Project-Level SDG Impact—Case Study of a Water Utility Company

Abstract: Achievement of the United Nations’ 2030 Global Goals for Sustainability is of paramount importance. However, for engineers and project managers to take meaningful action, they need the practical tools, processes and leadership to turn grand rhetoric into viable engineering solutions. Linking infrastructure project sustainability performance to sustainable development goals (SDG) targets is problematic. This article builds on the previous development of an innovative infrastructure business model, called the “I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the second group of studies, a number of recent works have focused on the organizational level to analyze the engagement with SDGs. Van Zanten and Van Tulder (2018) conducted a survey of 81 large MNCs from Europe and North America, and found that companies are more likely to engage with SDG targets relevant to their own value chain operations, and with targets that “avoid harm” rather than “do good.” Other scattered works analyzed indirectly organizational engagement with SDGs through limited case‐studies (e.g., Battaglia et al, 2020; Mansell et al, 2020; Vildåsen, 2018). For example, Battaglia et al (2020) analyzed the operational dimensions of the SDGs for the case of a large Italian energy company.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…In the second group of studies, a number of recent works have focused on the organizational level to analyze the engagement with SDGs. Van Zanten and Van Tulder (2018) conducted a survey of 81 large MNCs from Europe and North America, and found that companies are more likely to engage with SDG targets relevant to their own value chain operations, and with targets that “avoid harm” rather than “do good.” Other scattered works analyzed indirectly organizational engagement with SDGs through limited case‐studies (e.g., Battaglia et al, 2020; Mansell et al, 2020; Vildåsen, 2018). For example, Battaglia et al (2020) analyzed the operational dimensions of the SDGs for the case of a large Italian energy company.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…The research presented later shows this cannot currently be achieved, and the evidence [16,17] illustrates that the golden thread from project measurement to national/global level is missing. There is a gap between theory and practice [11,13]. The most significant global response to the planetary boundary challenge was in 2015, when all governments ratified the UN's 17 Sustainable Development Goals [4] (as shown in Figure 1), to be achieved by 2030 (with 169 targets and 244 indicators also agreed in 2017).…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…The research presented later shows this cannot currently be achieved, and the evidence [16,17] illustrates that the golden thread from project measurement to national/global level is missing. There is a gap between theory and practice [11,13]. In order to understand why there is a perceived gap, it is helpful to analyse the structural build of the SDG performance framework.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are part of the UN Resolution popularly known as "Agenda 2030". Research directions on this topic include responses to climate change [22][23][24][25], social equity, education and health [26][27][28][29][30][31], urban sustainability [32][33][34][35], sustainable business [36][37][38][39][40] and policy design, implementation and evaluation [41][42][43][44][45]. It is widely understood that the SDGs are closely interdependent and that their successful pursuit requires integration across most policy areas.…”
Section: Introductionmentioning
confidence: 99%